CHATGPT VS MANUAL TRANSLATION: A COMPARATIVE STUDY ON A TOURISM-FOCUSED BILINGUAL PROFILE BOOK - Purnamasari, Yessy; Zewitra, Zewitra; Bakhti, Krisna Yudha; Febryanto, Mohammad (Jurnal JOEPALLT (Journal of English Pedagogy, Linguistics, Literature, and Teaching), 2025)
The rapid development of artificial intelligence technology, particularly in machine translation systems such as ChatGPT, has prompted extensive discourse regarding its efficacy compared to manual translation. This study aims to compare the quality of manual and ChatGPT-generated translations within the context of a tourism-focused bilingual profile book of ‘Big Farmer’, focusing on three analytical levels: lexical, syntactic, and textual. Utilizing a qualitative approach, the research examines the differences in word choice, sentence structure, and semantic accuracy between human and machine translations. The findings reveal that although ChatGPT excels in terms of speed and consistency, manual translation remains superior in preserving cultural nuances and linguistic subtlety, especially at the syntactic and textual levels. Distinct from previous studies that predominantly explored scientific, legal, or medical texts, this research highlights the unique challenges of translating a bilingual profile book in the context of tourism, where maintaining tone and brand identity is paramount. This study contributes to translation studies both theoretically, by expanding the knowledge base in English-Indonesian translation, and practically, by providing insights for translators on the prudent application of AI technologies in translation practices.